The Discovery and Development of the N-Substituted trans-3,4-Dimethyl-4-(3′-hydroxyphenyl)piperidine Class of Pure Opioid Receptor Antagonists - Carroll, F. Ivy (ChemMedChem, 2014)
N -Substituted trans-3,4-dimethyl-4-(3-hydroxyphenyl)piperidines are a class of pure opioid receptor antagonists with a novel pharmacophore. This opioid receptor antagonist pharmacophore was used as a lead structure to design and develop several interesting and useful opioid receptor antagonists. In this review we describe: 1) early SAR studies that led to the discovery of LY255582 and analogues that are nonselective opioid receptor antagonists developed for the treatment of obesity; 2) the discovery and commercialization of LY246736 (alvimopan; ENTEREG®), a peripherally selective opioid receptor antagonist that accelerates the time to upper and lower GI recovery following surgeries that include partial bowel resection with primary anastomosis; and 3) the discovery and development of the potent and selective κ opioid receptor antagonist JDTic and analogues as potential pharmacotherapies for treating depression, anxiety, and substance abuse (nicotine, alcohol, and cocaine). In addition, the use of JDTic for obtaining the X-ray structure of the human κ opioid receptor is discussed.